PENGGUNAAN MEDIA KAHOOT SEBAGAI MEDIA EVALUASI PEMBELAJARAN KOSAKATA BAHASA ARAB DI SMP IT DARUL WAHDAH - Umairoh Ilma Ummu Amna; Suparmanto Suparmanto; Putri Lutfiyah; Ziki Ridwanullah; Azriel Zizoe Zainuddin; Muhammad Arif Rahmansyah (Diwan Media Pustaka, 2025)
The rapid development of educational technology requires assessment strategies that are more interactive, effective, and aligned with the characteristics of 21st-century learners. This study aimed to describe the use of Kahoot as an assessment tool for Arabic vocabulary learning and to examine the responses of teachers and students to its implementation at SMP IT Darul Wahdah. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, questionnaires, and documentation. The participants consisted of 31 eighth-grade students from classes VIII A and VIII B. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing and verification. The findings show that Kahoot increased students’ motivation, participation, and enthusiasm during assessment activities, while also helping teachers evaluate students’ understanding quickly and efficiently. Nevertheless, its implementation was constrained by limited technological facilities and unstable internet access. In conclusion, Kahoot is an effective innovative assessment medium, but its optimal use depends on adequate infrastructure and technological readiness. Future studies are recommended to apply experimental or quasi-experimental designs to measure more precisely the impact of Kahoot on Arabic vocabulary learning outcomes.